(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article, according to the information that has reached us, provides information about the existence of bilinguals of their time, the formation of bilingual history and information about the development of bilingual poetry. We know that the poem was written under the influence of the poet’s enlightened views, from the choice of thematic material to the presentation system, language, and vocabulary.